Clinical presentation, diagnostic findings, prognostic factors, treatment and outcome in dogs with meningoencephalomyelitis of unknown origin: A review. (February 2019) - Cornelis, I.; Van Ham, L.; Gielen, I.; De Decker, S.; Bhatti, S.F.M.
Highlights: Meningoencephalomyelitis of unknown aetiology (MUA) is an inflammatory idiopathic CNS disorder in dogs. Histopathology is the reference standard for diagnosis, but certain clinical diagnostic tools can be helpful. Prognosis remains guarded. Different treatment regimens and prognostic factors are described Abstract: Meningoencephalomyelitis of unknown origin (MUO) encompasses a group of idiopathic, most likely immune mediated, inflammatory central nervous system diseases that cause clinical, diagnostic and treatment challenges to veterinary neurologists. Clinical criteria for obtaining this presumptive diagnosis are currently available, and multiple treatment protocols have previously been investigated in small (prospective or retrospective) case series. As this group of diseases is considered fatal if left untreated, the identification of clinically usable prognostic indices could be of great value. This review provides an overview of recent developments in the clinical presentation, diagnostic findings, possible prognostic factors, treatment and outcome in dogs diagnosed with MUO.